A Hilbert-type integral inequality with its best extension - Weiliang, Wu; Donglan, Lian (Global Journal of Mathematical Analysis, 2015)
By using the way of weight function and the technique of real analysis, a new Â Hilbert-type integral inequality with a Â kernel as \(min{x^λ_1,y^λ_2}\) and its equivalent form are established. As application, the constant factor on the plane are the best value and its best extension form with some parameters and the reverse forms are also considered.